(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In this article the theoretical and methodological foundations of psycholinguistic approach to the correction of logoneurosis in primary grade students are analyzed. Logoneurosis is illuminated not as a disorder in the external expression of speech, but as a complex psycholinguistic phenomenon associated with the disruption of internal speech planning, semantic modeling, and grammatical coding processes. The study substantiates the main principles of psycholinguistic approach — the importance of activating internal speech planning, semantic priority, gradual increase of cognitive load, and the formation of speech automation in the elimination of logoneurosis. It is scientifically based that this approach serves to reorganize the child’s speech activity at the level of internal psychological mechanisms and is highly effective in the formation of stable, smooth and conscious speech in children of primary grade age.